JMJD5 is a human arginyl C-3 hydroxylase - Wilkins, S; Islam, M; Gannon, J; Markolovic, S; Hopkinson, R; Ge, W; Schofield, C; Chowdhury, R (Springer Nature, 2018)
Oxygenase catalysed post-translational modifications of basic protein residues including lysyl hydroxylations and Nε-methyl lysyl demethylations have important cellular roles. Jumonji-C (JmjC) domain-containing protein 5 (JMJD5), which genetic studies reveal is essential in animal development, is reported as a histone Nε-methyl lysine demethylase (KDM). Here we report how extensive screening with peptides based on JMJD5 interacting proteins led to the finding that JMJD5 catalyses stereoselective C-3 hydroxylation of arginine-residues in sequences from human regulator of chromosome condensation domain-containing protein 1 (RCCD1) and ribosomal protein S6 (RPS6). High-resolution crystallographic analyses reveal overall fold, active site and substrate binding/ product release features supporting the assignment of JMJD5 as an arginine hydroxylase rather than a KDM. The results will be useful in the development of selective oxygenase inhibitors for the treatment of cancer and genetic diseases.